Importance of virtual illumination technique in the illumination education - (:unkn) unknown (My University, 2010)
Fundamental topic of Illumination consists of production, distribution, economy and measurement of light. Besides, behaviors of people towards light are studied. Illumination is a major topic in electrical engineering and architecture in our age. Any field to be illuminated should be analyzed as a special problem. However, solution to the illumination problem can only be found by electrical engineers having a voice in light production and architects working together. Illumination education has only started in recent past in our country. In the past, in many applications too many or wrong type lighting fixtures were used mistakenly due to ignorance. Since illumination became a separate field in our universities, use of computers in illumination education has increased rapidly. Computers are used in preparing illumination projects both to measure and to visualize. A designer can make virtual and natural lighting measurements using computers. In general, computer programmers are used in illumination technique to design fixtures, to measure and evaluate interior and exterior lighting. In addition to this, virtual illumination technique should be used in education in order to be able to visualize the lighting projects in three dimensions. ©2010 IEEE.
Keywords: Illumination education; Virtual illumination